Pengaruh Penempatan dan Pelatihan Kerja terhadap Kinerja Karyawan PT. Ej International Eyelashes - Diana Pramudya Wardhani; Nenden Nur Annisa; Deria Dwi Elfarina (Sekolah Tinggi Ilmu Ekonomi AMM, 2023)
A company needs human resources to organize, manage, run, and control the resources owned by the company. Companies generally expect good performance from each employee in carrying out the tasks assigned by the company. Quality employees are able to realize the aspirations and goals of the company by presenting good performance. This study aims to examine the effect of placement on employee performance, examine the effect of job training on employee performance. The population in this study were all employees of PT. EJ International Eyelashes Purworejo. The sampling technique in this study used a saturated sample and obtained a sample of 95 respondents. The data collection instrument used a questionnaire with a Likert scale that had been tested and met the validity and reliability requirements. Data analysis used multiple linear regression analysis using SPSS 22.0 for windows. The conclusion of this study is that placement has a positive and significant effect on employee performance, job training has a positive and significant effect on employee performance.